Evaluation of the taste-masking effects of (2-hydroxypropyl)-β-cyclodextrin on ranitidine hydrochloride; a combined biosensor, spectroscopic and molecular modelling assessment. Issue 7 (17th January 2018) - Chay, Sai Kin; Keating, Alison V.; James, Colin; Aliev, Abil E.; Haider, Shozeb; Craig, Duncan Q. M.
Abstract : A correlation between taste masking, assessed using a taste sensor system, and inclusion complex formation, assessed using NMR and molecular docking studies, has been identified for ranitidine HCl and (2-hydroxypropyl)-β-cyclodextrin. Abstract : Taste assessment in an increasingly important aspect of formulation development, particularly for paediatric medications. Electronic taste sensing systems have the potential to offer a rapid, objective and safe method of taste assessment prior to the use of more costly human panels or animal models. In this study, the ability of the TS-5000Z taste sensing system to assess the taste masking efficiency of (2-hydroxypropyl)-β-cyclodextrin (HP-β-CyD) complexes with ranitidine hydrochloride was evaluated in order to explore the potential of the biosensor approach as a means of assessing taste masking by inclusion complexation. Nuclear magnetic resonance (NMR) spectroscopy and molecular docking studies were employed to identify and examine the interaction between ranitidine hydrochloride and HP-β-CyD. Taste-masking efficiencies were determined by the Euclidean distance between taste-masked formulations and the pure drug substance on a PCA score plot. The results showed that with increasing molarity of HP-β-CyD in the formulation, the distance from ranitidine hydrochloride increased, thus indicating a significant difference between the taste of the formulation and that of the pure drug. NMR studies also provided strong supporting evidence for the complexation between HP-β-CyD and ranitidine hydrochloride, with the H3′ region of the former identified as the most likely binding site for the drug. Molecular docking studies suggested that the dimethylamino and diamine groups of the drug form direct hydrogen bonds with the hydroxyl oxygen atoms of HP-β-CyD, while the furan ring docks in close proximity to H3′. This study has demonstrated that the biosensor system may provide quantitative data to assess bitterness of inclusion complexes with HP-β-CyD, while spectroscopic and modelling studies may provide a mechanistic explanation for the taste masking process. This in turn suggests that there is a role for biosensor approaches in providing early screening for taste masking using inclusion complexation and that the combination with mechanistic studies may provide insights into the molecular basis of taste and taste masking.